Characterization of the Function of Two S1Fa-Like Family Genes From Populus trichocarpa - Zhao, Huimin; Niu, Yani; Dong, Hao; Jia, Yaqi; Wang, Yucheng (Frontiers in Plant Science, 2021)
ABSTRACT S1Fa-like transcription factors (TFs) are small molecular weight proteins that contain both nuclear localization and DNA binding domains. However, the functions of S1Fa like TFs are poorly understood. In the present study, we identified the S1Fa-like TFs from the Populus trichocarpa genome, which revealed two S1Fa-like TF genes, PtS1Fa1 and PtS1Fa2. PtS1Fa1 and PtS1Fa2 expression was suppressed by drought and salt stress, and was also significantly altered by ABA, MeJA or SA treatment, Both PtS1Fa1 and PtS1Fa2 are nuclear proteins. Transgenic P. trichocarpa plants overexpressing PtS1Fa1 and PtS1Fa2, respectively, were generated. The plants overexpressing PtS1Fa2 showed increased fresh weight, chlorophyll content, and root length and weight compared with those in wild-type (WT) P. trichocarpa under drought conditions. Meanwhile, these phenotype traits of plants overexpressing PtS1Fa1 were similar to those of WT plants. Furthermore, overexpression of PtS1Fa2 reduced the malondialdehyde content, electrolyte leakage, H2O2 and O2- contents, and increased superoxide dismutase (SOD) and peroxidase (POD) activities. The expression of SOD and POD was also induced by PtS1Fa2. However, overexpression of PtS1Fa1 failed to affect any of these physiological parameters or SOD and POD gene expression. These results suggested that PtS1Fa2 plays a role in drought tolerance, and confers drought tolerance by increase antioxidant activity to reduce reactive oxygen species accumulation.